The long‐term impact of acute renal failure after aortic arch replacement for acute type A aortic dissection. Issue 8 (17th May 2022) - Brown, James A.; Serna‐Gallegos, Derek; Navid, Forozan; Thoma, Floyd W.; Zhu, Jianhui; Kumar, Rishabh; Aranda‐Michel, Edgar; Bianco, Valentino; Yousef, Sarah; Sultan, Ibrahim
Abstract: Objective: To determine the long‐term impact of developing acute renal failure (ARF) on survival after open aortic arch reconstruction for acute type A aortic dissection (ATAAD). Methods: This was an observational study of consecutive aortic surgeries from 2007 to 2021. Patients with ATAAD were identified via a prospectively maintained institutional database and were stratified by the presence or absence of postoperative ARF (by RIFLE criteria). Kaplan–Meier survival estimation and multivariable Cox regression analysis were performed. Results: A total of 601 patients undergoing open surgery for ATAAD were identified, of which 516 (85.9%) did not develop postoperative ARF, while 85 (14.1%) developed ARF, with a median follow‐up time of 4.6 years (1.6, 7.9). Baseline characteristics were similar across each group, except for higher rates of branch vessel malperfusion and lower preoperative ejection fraction in the ARF group. Patients with ARF underwent more total arch replacement and elephant trunk procedures, with longer cardiopulmonary bypass and circulatory arrest times than patients without ARF. ARF was associated with worse short‐term outcomes, including increased in‐hospital mortality, prolonged mechanical ventilation, higher rates of sepsis, more blood transfusions, and longer length of hospital stay. Unadjusted Kaplan–Meier survival estimates were significantly lower in the ARF group, compared to the group without ARF ( p  < .001, log‐rank test). After multivariable adjustment, the development of postoperative ARF was significantly associated with an increased hazard of death over the study's follow‐up time‐period (hazard ratio: 2.74, 95% confidence interval: 1.95, 3.86, p  < .001). Conclusions: ARF is a highly morbid postoperative event that may adversely impact long‐term survival after aortic surgery.